Codes of Finance : Engineering Derivatives in a Global Bank - Lepinay, Vincent Antonin (Book collections on Project MUSE., 2011)
The financial industry's invention of complex products such as credit default swaps and other derivatives has been widely blamed for triggering the global financial crisis of 2008. Codes of Finance takes readers behind the scenes of the equity derivatives business at one of the world's leading investment banks before the crisis, providing a detailed firsthand account of the creation, marketing, selling, accounting, and management of these financial instruments--and of how they ultimately created havoc inside and outside the bank. Vincent Antonin Lepinay, a former employee of the bank, investig.